Marjorie Swann, Environment, Society, and The Compleat Angler - Lokensgard, Kenneth Hayes (Journal for the study of religion, nature and culture, 2024)
Marjorie Swann, Environment, Society, and The Compleat Angler (University Park: The Pennsylvania State University Press, 2023), 270 pp., $ 124.95 (cloth), ISBN: 978-0-271-09519-6